Attitudes of Medical Students Toward the Care of the Dying in Relation to Personality Traits: Harm Avoidance and Self-Directedness Make a Difference. (December 2015) - Leombruni, Paolo; Miniotti, Marco; Zizzi, Francesca; Sica, Chiara; Bovero, Andrea; Castelli, Lorys; Torta, Riccardo
Caring for dying patients requires specific attitudes. Medical students often feel unprepared to cope with issues related to end-of-life care. Little is known about the relationships between personality and attitudes toward the dying; consequently, it is difficult for medical educators to devise training that is best suited to prepare students for practicing palliative medicine. The study aimed to investigate the role of personality in predicting students' attitudes toward the care of the dying. The study findings suggest a significant link between more self-directed and less harm-avoidant personality profiles and more developed attitudes toward the dying. Personality assessment in medical curricula is important, not merely to help teachers plan tailored training but also to foster in future doctors the propensity to develop a patient-centered practice.